Microstructural characterisation of TiAlTiAu and TiAlPdAu ohmic contacts to AlGaN/GaN - Fay, Mike W.; Harrison, Ian; Birbeck, J.C.; Hughes, B.T.; Uren, M.J.; Martin, T.; Brown, Paul D. (IOP Publishing Ltd, 2001)
Ti/Al/Ti/Au and Ti/Al/Pd/Au contacts to AlGaN/GaN have been investigated to ascertain the effect of annealing temperature on the structural evolution of the contacts. Ti/Al/Ti/Au contacts become ohmic after rapid thermal annealing at 750°C or higher, corresponding to the formation of an interfacial TiN phase, with inclusions penetrating through the AlGaN layer observed after annealing at 950°C. The Pd layer is shown to be more efficient at inhibiting diffusion of Au to the interface than Ti. Ohmic behaviour was not seen with the Ti/Al/Pd/Au scheme. Either the presence of Au at the interface may improve ohmic behaviour, or the Ti:Al ratio is insufficient in this scheme.